Seven Students' Activities: A Case Study on Rumah Tahfidz An-Nur Daily Routine and Memorization Levels - Rahman, Ikhwan; Nisa, Khairun; Saputri, Ranti Eka (International Journal of Multidisciplinary Research of Higher Education, 2020)
Rumah Tahfidz is a rich environment with a variety of activities that form the daily routine of the students. This research aims to look at the activities carried out in the Rumah Tahfidz and the extent of memorization by the students in the Rumah Tahfidz An-Nur. This research uses a qualitative method with a case study type of research. Data was taken from observation, namely through direct observation from the field and conducting interviews, and analyzed thematically. Then the data was analyzed using the Miles & Huberman interactive analysis model technique. The research results show that there are seven activities in Rumah Tahfidz An-Nur, such as: i) praying, ii) nasyid, iii) introduction to tajwid and practicing tajwid, iv) congregational prayer, v) Murajaah, vi) increasing memorization, vii) memorization test. The results of this research can be used as initial data for future researchers in studying this problem in the context of different issues.